DIVIDEND POLICY STRATEGY: Moderating the Effect of Financial Conditions and Investment Opportunities on Corporate Profit Growth - Mahendra, Made Indra (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to determine the effect of the company's financial condition and investment opportunity set on profit growth with dividend policy as a moderation in food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange in 2016-2021. The type of research used is quantitative associative. The data used are secondary data obtained from the Indonesia Stock Exchange for the research period. Sample selection was carried out based on the purposive sampling method with certain criteria so that 19 company samples were obtained. Data processing using statistical program eviews version 10. The research method uses regression analysis, namely t test, f test and moderated regression analysis. The results of the t test show that the company's financial condition has a positive and significant effect on profit growth, the investment opportunity set has a positive and significant effect on profit growth, the company's financial condition and investment opportunity set simultaneously affect profit growth, and the dividend policy is able to moderate the investment opportunity set on profit growth. However, the dividend policy does not moderate the company's financial condition against Profit growth in food and beverage sector companies for the 2016-2021 period.